2019
DOI: 10.3390/w11040728
|View full text |Cite|
|
Sign up to set email alerts
|

Water Footprint of Meat Analogs: Selected Indicators According to Life Cycle Assessment

Abstract: Animal-based products reportedly have substantial water footprints. One alternative to meat products is meat analogs, which are processed plant-based foods mimicking real meat products. As data for the water footprints of meat analogs are limited, the present study assesses their water consumption and their potential for contributing to eutrophication and ecotoxicity in fresh and marine receiving waters. Life cycle assessments, which encompassed the generation of ingredients to the packaging of products, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Limited data exists on how much plant-based substitutes exacerbate eutrophication, but existing research suggests they provide significant benefits over conventional meats. One study found that the average freshwater eutrophication potential of plant-based substitutes was an order of magnitude smaller than that of conventional pork sausage patties, and two orders of magnitude smaller than those of beef and chicken patties (Fresán et al, 2019). Another study found that conventional pork production resulted in six times greater eutrophication potential and required 3.4 times more fertilizer per unit of protein compared to a pea-based plantbased substitute (Zhu and van Ierland, 2004).…”
Section: Eutrophicationmentioning
confidence: 99%
“…Limited data exists on how much plant-based substitutes exacerbate eutrophication, but existing research suggests they provide significant benefits over conventional meats. One study found that the average freshwater eutrophication potential of plant-based substitutes was an order of magnitude smaller than that of conventional pork sausage patties, and two orders of magnitude smaller than those of beef and chicken patties (Fresán et al, 2019). Another study found that conventional pork production resulted in six times greater eutrophication potential and required 3.4 times more fertilizer per unit of protein compared to a pea-based plantbased substitute (Zhu and van Ierland, 2004).…”
Section: Eutrophicationmentioning
confidence: 99%
“…Indeed, highly processed plant-based ingredients have been highlighted as having a greater impact on resources and the environment than their lesser-processed counterparts [9]. The highly-processed, soy-derived components of our reported products may be largely responsible for the water consumption value we reported in our paper [1].…”
Section: Water Consumption Of Ingredients Included In Meat Analogsmentioning
confidence: 65%
“…In addition, we have modified the table so that water footprints for the unprocessed meats have been drawn exclusively from LCA studies rather than water footprint assessment (WFA) studies. As we discussed in the original paper [1], comparing values calculated from the WFA or even closely related LCA methodologies can be problematic as a result of the differences in the assumptions and algorithms employed to calculate those values [5]. As such, the WFA data presented by Berardy et al [8] from the publications by Hoekstra [15] and Mekonnen and Hoekstra [16] have been removed.…”
Section: Data Published In the Literaturementioning
confidence: 99%
See 2 more Smart Citations